2018
DOI: 10.17712/nsj.2018.3.20180058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders among patients attending primary health care centers in the capital of Saudi Arabia

Abstract: The prevalence of mental disorders was slight high. The rates of untreated mental disorders necessitate the healthcare makers in Kingdom of Saudi Arabia to implement efficient strategies to halt the progression of untreated mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
2
16
0
1
Order By: Relevance
“…Worldwide, there is growing concern about depression among adult people [38] and Saudi Arabia is not an exception. Additionally, the integration of mental health services at primary care centres in Saudi Arabia is challenging [39]. Thus, there is a need to screen patients attending primary care centres, particularly those of middle age for depression as one of the commonest psychiatric disorders which would help in providing the real situation of psychiatric disorder burden at PHC centres in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, there is growing concern about depression among adult people [38] and Saudi Arabia is not an exception. Additionally, the integration of mental health services at primary care centres in Saudi Arabia is challenging [39]. Thus, there is a need to screen patients attending primary care centres, particularly those of middle age for depression as one of the commonest psychiatric disorders which would help in providing the real situation of psychiatric disorder burden at PHC centres in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the prevalence of depression among young adult patients (20-40 years) attending primary healthcare centres in Tabuk was 74%; being mild among 37.8%, moderate among 20.8% whereas moderately severe to severe among 15.4% of them. In a study carried out previously among patients attending primary health care centres in Riyadh [39], a rate of 33.4% has been reported. In a similar study carried out in Northern Province in Sri Lanka [40], the prevalence of mild depression was 13.3% whereas that of major depression was 4.5% in adult patients attending primary care settings.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing concern about the burden and effect of mental disorders on people’s health, their social lives, and economies worldwide [ 7 ]. It was found that among 160 patients who attended primary healthcare centers in the capital of Saudi Arabia during three months in 2017, 28.5% reported cases of mental health disorders [ 8 ]. Further, the Saudi National Health & Stress Survey reported that 2 in 5 Saudi youth meet the criteria for having a mental health condition sometime in their life and only 5% of Saudis seek professional treatment for their mental illness [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com o SRQ-20, o sofrimento psicológico esteve presente em 22,7% das mulheres avaliadas neste estudo. Dados revelam que este é um fenômeno prevalente 43 em diferentes países, como demonstrado no estudo de Alghadeer et al 44 , realizado na cidade de Riyadh, na Arábia Saudita, em que 28,5% da população atendida pela atenção primária apresentava problemas de saúde mental.…”
Section: Discussionunclassified